2003
DOI: 10.1061/(asce)0733-9372(2003)129:11(975)
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Annual Average Daily Traffic on Highway Runoff Pollutant Concentrations

Abstract: The objective of this study was to evaluate correlations between annual average daily traffic (AADT) and storm water runoff pollutant concentrations generated from California Department of Transportation (Caltrans) highway sites. Analyses of data collected from the Caltrans Cyear (1997-01) highway runoff characterization program revealed that, in general, pollutant concentrations from urban highways were higher than those found from non-urban highways. For a limited number of pollutants, however, the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 9 publications
4
87
1
1
Order By: Relevance
“…The EC measured in the influent water is comparable to other studies [30][31][32] and was seen to increase from influent to percolate, reflecting that the water mobilized various ions as it passed through the soil.…”
Section: Influent and Percolate Concentrationssupporting
confidence: 71%
See 2 more Smart Citations
“…The EC measured in the influent water is comparable to other studies [30][31][32] and was seen to increase from influent to percolate, reflecting that the water mobilized various ions as it passed through the soil.…”
Section: Influent and Percolate Concentrationssupporting
confidence: 71%
“…The observed concentration of less than 50 mg/L of SS in the influent from both Odense and Copenhagen (Table 7) is relatively low compared to other studies [30][31][32], but was most likely due to the low traffic level in the areas. In the swale-trench systems in Odense the SS measured in the percolate is half of what is observed in the influent.…”
Section: Influent and Percolate Concentrationsmentioning
confidence: 64%
See 1 more Smart Citation
“…These results are consistent with those obtained by Fewtrell and Kay (2007) who observed that ADWP can markedly affect the quality of runoff water. Kayhanian et al (2003) used multiple linear regression analysis on data collected in California to find a statistically significant effect of ADWP on runoff concentrations for 25 of the 33 constituents tested. Twenty-three of the significant regressions had a positive coefficient (i.e., concentrations increase with longer ADWPs) with only two (pH and diazinon) showing a negative value.…”
Section: Effect Of Rainfall Characteristics On Roof Runoff Water Qualitymentioning
confidence: 99%
“…The values obtained by Kayhanian et al (2003) have been taken as typical and their maximum values were selected as the basis of the input values for the simulations reported in this paper because they appear to represent 'worst-case' input contaminant loadings. Leachate concentration values were obtained from an earlier study by Hill (2004) who tested a wide range of conventional and alternative aggregates that might be used as base course materials.…”
Section: Parametersmentioning
confidence: 99%